Hubungan Electronic Health Literacy dengan Penerapan Gaya Hidup Sehat pada Mahasiswa S1 Keperawatan Universitas Andalas - Roza Armayuni; Esthika Ariany Maisa; Susmiati Susmiati (Universitas Pahlawan Tuanku Tambusai, 2025)
College students are vulnerable to unhealthy lifestyles such as lack of medical check-up and low levels of physical activity. Electronic health literacy is one of the factors that contributes to a person's healthy lifestyle. This study aims to determine the correlation between electronic health literacy and nursing students healthy lifestyles at Andalas University. This research is a quantitative study with a correlational design and cross sectional approach. It was conducted from September 2023 - July 2024 with 250 respondents taken using the proportional stratified random sampling technique. Data collection using the Electronic Health Literacy Scale (E-HEALS) and Health Promotion Lifestyle Profile II questionnaires (HPLP II). The median of electronic health literacy was 32,00 categoried as high electronic health literacy and healthy lifestyles was 126,00 categoried as moderate. After conducting Spearman statistical test, it found that there was a positive significant with a moderate relationship between electronic health literacy and the application of healthy lifestyle in respondents (p = 0,000, r = 0,453, r2 = 0,227). It is expected that nursing students can improve their electronic health literacy and healthy lifestyle behaviour by improving their basic knowledge and skills of both.